The semiotics of tacit knowledge sharing: a study from the perspective of symbolic interactionism - LILIAN APARECIDA PASQUINI MIGUEL (Cadernos EBAPE.BR)
Abstract This article proposes an integrated theoretical model, combining Polanyi and Peirce constructs - tacit knowledge and semiotics, respectively - under the symbolic interactionist perspective. It aims to understand how signs are manifested as mediators in the tacit knowledge sharing process among members of a cooperative organization. It is based on: a theoretical articulation of the principles of tacit knowledge, which defends the ineffability of this kind of knowledge; semiotic theory, in which signs are a representation of “something for someone” and imply that everything in the world is a sign; and the symbolic interactionist view. This theoretical integration presents a significant theoretical contribution because it proposes a process of semiotic perception to tacit knowledge sharing. This perspective suggests that tacit knowledge sharing occurs through symbolic interaction, mediated by semiotics; this innovative model depends both on internal and external conditions, albeit involving aspects outside organizational control.